Performance evaluation of wire electro-discharge machining on tungsten carbide - Hassan, Mas Ayu (2006)
This thesis presents the machining of tungsten carbide (WC-15%Co) using wire electro-discharge machining (WEDM) with brass wire diameter of 0.2 mm used as the tool electrode. The main purpose of this study was to investigate the influenced of various parameters involved in WEDM on the machining characteristics, namely, surface roughness (Ra), sparking gap (Gap), cutting speed (CS), recast layer (RL) and microcracks after undergone WEDM process. The Full Factorial Design of Experiment (DOE) approach with two-level was used to formulate the experimental layout, to analyze the effect of each parameter on the machining characteristics and to predict the optimal setting for each WEDM parameters such as pulse on (ON), pulse off (OFF), peak current (IP) and servo voltage (SV). Confirmation tests were also conducted for the optimum conditions for each machining characteristics in order to verify and compare the results from the theoretical prediction using Design Expert software and experimental confirmation tests. In this investigation, the machining operation for tungsten carbide was performed using a Sodick linear motor WEDM series AQ537L. Meanwhile, for the measurement equipments; Mitutoyo Formtracer CS-5000 was used to measure the Ra, Zeiss Axiotech High Power Optical Microscope was used to measure the Gap and lastly, the thickness of recast layer and the presence of microcracks were examined using the Scanning Electron Microscope XL40. In general, results revealed that pulse on have appeared to be the significant effect to all responses investigated. Overall, the results from the confirmation tests showed that the percentage of performance was acceptable due to all the results obtained were within the allowable values which was less than 10% of margin error.